Sources and characteristics of size-resolved particulate organic acids and methanesulfonate in a coastal megacity: Manila, Philippines - Stahl, Connor (Archīum Ateneo, 2020)
A 16-month (July 2018–October 2019) dataset of size-resolved aerosol composition is used to examine the sources and characteristics of five organic acids (oxalate, succinate, adipate, maleate, phthalate) and methanesulfonate (MSA) in Metro Manila, Philippines. As one of the most polluted megacities globally, Metro Manila offers a view of how diverse sources and meteorology impact the relative amounts and size distributions of these species. A total of 66 sample sets were collected with a Micro-Orifice Uniform Deposit Impactor (MOUDI), of which 54 sets were analyzed for composition. Organic acids and MSA surprisingly were less abundant than in other global regions that are also densely populated. The combined species accounted for an average of 0.80 ± 0.66 % of total gravimetric mass between 0.056 and 18 µm, still leaving 33.74 % of mass unaccounted for after considering black carbon and water-soluble ions and elements. The unresolved mass is suggested to consist of non-water-soluble metals as well as both water-soluble and non-water-soluble organics. Oxalate was approximately an order of magnitude more abundant than the other five species (149 ± 94 ng m−3 versus others being < 10 ng m−3) across the 0.056–18 µm size range. Both positive matrix factorization (PMF) and correlation analysis are conducted with tracer species to investigate the possible sources of organic acids and MSA. Enhanced biomass burning influence in the 2018 southwest monsoon resulted in especially high levels of submicrometer succinate, MSA, oxalate, and phthalate. Peculiarly, MSA had negligible contributions from marine sources but instead was linked to biomass burning and combustion. Enhanced precipitation during the two monsoon seasons (8 June–4 October 2018 and 14 June–7 October 2019) coincided with a stronger influence from local emissions rather than long-range transport, leading to notable concentration enhancements in both the sub- and supermicrometer ranges for some species (e.g., maleate and phthalate). While secondary formation via gas-to-particle conversion is consistent with submicrometer peaks for the organic acids and MSA, several species (i.e., phthalate, adipate, succinate, oxalate) exhibited a prominent peak in the coarse mode, largely owing to their association with crustal emissions (i.e., more alkaline aerosol type) rather than sea salt. Oxalate's strong association with sulfate in the submicrometer mode supports an aqueous-phase formation pathway for the study region. However, high concentrations during periods of low rain and high solar radiation suggest photo-oxidation is an important formation pathway.